Boot & Shoe - Frazee, Marla (New York : Beach Lane Books, 2012)
Boot and Shoe are dogs that live in the same house, eat from the same bowl, and sleep in the same bed but spend their days on separate porches until a squirrel mixes things up.
School Library Journal starred, August 2012.
Booklist starred, August 2012.
Kirkus Starred, September 2012.
Horn Book, September 2012.
School Library Journal starred.
Booklist starred.
Keywords: Solitude -- Juvenile fiction; Dogs -- Juvenile fiction; Solitude -- Fiction; Dogs -- Fiction; Solitude -- Fiction; Dogs -- Fiction; Solitude -- Fiction; Dogs -- Fiction; Picture books for children